Ok, I have two question that have me stuck. I understand heavyside functions and how to do a laplace transform on them but, they've thrown me a curve ball. I'm sure I'm just making it more complicated then it needs to be. Here is problem number one. g(t) = 2t for 0 <= t < 1; 2 for 1 <= t; This is the same as: g(t) = 2tH(t) - 2tH(t-1) + 2H(t-1) The next step is were I'm confused. The book finished setting up this problem for a laplace transform by changing the equation to this: g(t) = 2tH(t) - 2(t-1)H(t-1) Why did they change it like this and how did they do this. I'm know I'm over looking something but, I'm not sure what. Any help would be great.